Glutamatergic Neurons in the Amygdala Are Involved in Paclitaxel-Induced Pain and Anxiety - Liu, Jiaxin; Li, Dangchao; Huang, Jing; Cao, Jing; Cai, Guohong; Guo, Yuexian; Wang, Guiying; Zhao, Shuang; Wang, Xiuli; Wu, Shengxi (Frontiers in Psychiatry, 2022)
Paclitaxel is widely used as a first-line chemotherapy agent to treat malignant tumors. However, paclitaxel causes peripheral nerve fiber damage and neuropathic pain in some patients. In addition, patients received paclitaxel chemotherapy are often accompanied by negative emotions such as anxiety. The amygdala is critically involved in regulating pain signals, as well as anxiety. The purpose of this study is to clarify the role of Ca2+/calmodulin-dependent protein kinase II (CaMKII) -positive glutamatergic neurons in the amygdala in paclitaxel-induced pain and negative affective symptoms. Intraperitoneal injection of paclitaxel into mice caused mechanical and thermal allodynia, as measured by Von Frey test and Hargreaves test, and anxiety, as measured by open field test and elevated plus maze test. Immunofluorescence staining revealed that c-fos-positive neurons were significantly more in the basolateral amygdala (BLA) and central amygdala (CeA) in paclitaxel-treated mice than untreated mice. Furthermore, part of c-fos-positive neurons in the BLA were immunoreactive of CaMKII. Engineered Designer receptors exclusively activated by designer drugs (DREADD) receptor hM4Di or hM3Dq was selectively expressed on CaMKII neurons by injection of adeno-associated virus (AAV) vectors containing CaMKII and hM4Di or hM3Dq. Administration of DREADD agonist CNO to selectively inhibit the CaMKII neurons in the BLA significantly increased the thresholds for mechanical and thermal pain. In addition, selectively inhibition of CaMKII neurons in the BLA alleviated anxiety behavior without affecting the motor activity. In summary, our findings suggest that CaMKII neurons in the amygdala are critical for neuropathic pain and anxiety behaviors induced by paclitaxel chemotherapy.